The Role of Lipid Metabolism Disorders in Rhinitis and Asthma - Wu, Muyun; Cheng, Jieli; Wen, Yuqin; Cheng, Jing (Combinatorial Chemistry & High Throughput Screening, 2026)
The current core theory of rhinitis and asthma is referred to as the antigen-antibody theory. However, the academic perspective is insufficient to explain the issues that arise in the epidemiology, pathophysiology, and clinical treatment of these diseases. So, the academic field of lipid metabolism disorders emerged. This perspective aims to explore two aspects: firstly, the overall approach and definition (starting with a new origin of the digestive tract rather than antigens from the respiratory tract; the non-digestion of various nutrients and the effects of probiotics result in a series of pathological and physiological changes in the body) and secondly, key aspects, such as 1. Dietary factors and lipid disorders that occur first, followed by airway hyperresponsiveness and asthma; 2. The prominent role of lipid droplet morphology in mast cells manifested as a bridge between lipid metabolites and lipid mediators released during allergies; and 3. Low-energy diet intervention with a significant effect on patients. This perspective offers valuable insights into new factors for the primary prevention of these diseases and exploring new avenues for the treatment of such diseases.
Keywords: diet